Activator Protein-1 Transcriptional Activity Drives Soluble Micrograft-Mediated Cell Migration and Promotes the Matrix Remodeling Machinery - Martina Balli; Jonathan Sai-Hong Chui; Paraskevi Athanasouli; Willy Antoni Abreu de Oliveira; Youssef El Laithy; Maurilio Sampaolesi; Frederic Lluis (Stem Cells International)
Impaired wound healing and tissue regeneration have severe consequences on the patient’s quality of life. Micrograft therapies are emerging as promising and affordable alternatives to improve skin regeneration by enhancing the endogenous wound repair processes. However, the molecular mechanisms underpinning the beneficial effects of the micrograft treatments remain largely unknown. In this study, we identified the active protein-1 (AP-1) member Fos-related antigen-1 (Fra-1) to play a central role in the extracellular signal-regulated kinase- (ERK-) mediated enhanced cell migratory capacity of soluble micrograft-treated mouse adult fibroblasts and in the human keratinocyte cell model. Accordingly, we show that increased micrograft-dependent in vitro cell migration and matrix metalloprotease activity is abolished upon inhibition of AP-1. Furthermore, soluble micrograft treatment leads to increased expression and posttranslational phosphorylation of Fra-1 and c-Jun, resulting in the upregulation of wound healing-associated genes mainly involved in the regulation of cell migration. Collectively, our work provides insights into the molecular mechanisms behind the cell-free micrograft treatment, which might contribute to future advances in wound repair therapies.